Lymphedema pathogenesis involves antigen-driven expansion of CD4+ T cells in skin - Campbell, Adana-Christine; Stull-Lane, Annica R.; Baik, Jung Eun; Sarker, Ananta; Shin, Jinyeon; Ashokan, Gopika; Park, Hyeung Ju; Pollack, Bracha L.; Pakkerakari, Pradhi; Parisotto, Yollanda Franco; Roberts, Arielle; Brown, Chrysothemis C.; et al. (Frontiers in Immunology, 2025)
IntroductionLymphedema, a progressive condition involving unresolved swelling and inflammation, affects as many as 1 in 1000 Americans. Although CD4+ T cells are implicated in the chronic inflammatory process, antigen-specific responses are understudied.MethodsUsing high-throughput sequencing, we studied the T cell receptors (TCRs) of CD4+ T cells in paired normal and lymphedema skin biopsies of 11 patients. We also employed in vitro studies using human samples and cells from a lymphedema mouse model.ResultsTarget epitopes of the TCRs, including the antigen insulin, were identified. Clonality was significantly higher in lymphedema samples than in controls, both in human samples and a mouse model of the disease. In vitro studies using human samples and a lymphedema mouse model demonstrated increased activated memory T cell responses specific to the antigen insulin compared with the control.DiscussionOur study highlights an oligoclonal expansion of CD4+ T cells in lymphedema and supports insulin as a probable antigen driving T cell responses. These findings can help inform more precise therapeutic targets for the development of better therapies and preventative tools to combat lymphedema progression.